"Marrying Out" for Love: Women's Narratives of Polygyny and Alternative Marriage Choices in Contemporary Senegal. (5th April 2016) - Kringelbach, Hélène Neveu
Abstract: This article examines the ways in which childhood and youth experiences of living in polygynous households shape the aspirations of middle-class Muslim Senegalese women to companionate marriage. Increasingly, such aspirations are fulfilled through marriage with European men. In contrast to an enduring popular discourse according to which women live happily with polygyny throughout the Senegambian region, this article shows how some middle-class women's choice to "marry out" is explicitly linked to family narratives and personal experiences of suffering. In a context in which many of these women face strong familial opposition to marriage with non-Muslim European men, this article suggests that the women's narratives provide moral legitimacy to their "alternative" choices. Résumé: Cet article examine comment et de quelles manières les expériences des enfants et des jeunes qui vivent dans des ménages polygames, façonnent les aspirations des femmes sénégalaises musulmanes de la classe moyenne au mariage de compagnonnage. De plus en plus, de telles aspirations sont satisfaites par le mariage avec des hommes européens. Contrairement à un discours populaire qui perdure selon lequel les femmes vivent heureuses dans la polygynie dans toute la région de Sénégambie, cet article montre comment le choix de certaines femmes de la classe moyenne à «se marier en dehors» est explicitement lié à des récits de famille et des expériences de souffrances personnelles. Cet article suggère que les récits des femmes assurent la légitimité morale à leurs choix "alternatifs" dans un contexte où beaucoup d'entre elles font face à une forte opposition familiale au mariage avec des hommes européens non-musulmans.